Similarities and Differences Between Bullying and Sexual Harassment in Schools: A Social-Ecological Review of Risk and Protective Factors - Zehra Sahin-Ilkorkor; Sarah Jane Brubaker (Behavioral Sciences)
In this conceptual article, the authors provide a narrative review of literature on bullying and sexual harassment in K-12 schools framed through a comparative analysis of risk and protective factors for both forms of violence across the social-ecological spectrum. We find that a greater number of studies of both forms of violence focus on student and microsystem-level factors rather than on higher levels of the ecosystem including school boards, neighborhoods, and broader cultural norms. In addition, the research overwhelmingly identifies more risk factors than protective factors. Finally, we find more similarities than differences in risk and protective factors between the two forms of school-based violence. We identify implications of the findings for theory, research, and policy and suggest that preventing any form of harassment at school will benefit not only students but the entire school community. We argue that the causes of school-based harassment are complex and require comprehensive prevention, intervention, and response approaches that address shared risk and protective factors, particularly those at the community and mesosystem, exosystem, and macrosystem levels. Ultimately, we argue that all community stakeholders must be committed to and engaged in these endeavors for them to be successful.